Significance of real-time petro-physical data for an optimal remote geosteering operation in complex geological reservoirs - Amer, Muhammad Attique; Ehsan, Muhsan; Akhtar, Muhammad Javid (Geology, Geophysics and Environment, 2021)
In the last decade, the oil industry has transitioned from primarily drilling vertical wells to a majority of extended reach complex horizontal wells with help of geosteering techniques for better reservoir and production efficiencies. The overall objective of geosteering and well placement has helped to maximize reservoir contact by the keeping well trajectory in the pay zone with the help of quality real-time data, especially in these uncertain times of pandemic due to COVID-19. This paper illustrates the immense impact of real-time data feeds (special logging tools/images) at operation centers with the full remote expert support of multidisciplinary teams. The proper data communication mechanism is also helpful to share the information across asset teams in a timely manner to drill complex wells remotely. To achieve the desired geosteering objective, experts monitor and evaluate the real-time petro-physical data of a landing well and design the well path accordingly to stay in the pay zone/horizon. During this collaborative and integrated geosteering process, the geological and petro-physical variables like the reservoir architecture, permeability and porosity distribution, and fluid contacts are also being used to update the reservoir models in real-time, based on the latest subsurface information for better reservoir management, operational performance and timely decision making.